2015
DOI: 10.1177/1060028015592215
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Versus Diclofenac in Mild to Moderate Depression Management Among Breast Cancer Patients

Abstract: Celecoxib seems to possess superior antidepressive effects compared with diclofenac in breast cancer patients with mild to moderate depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 46 publications
0
45
0
Order By: Relevance
“…Theoretically, higher doses of aspirin might inhibit COX‐2 and thereby increases leukocyte recruitment into the brain potentially causing tissue damage . The non‐aspirin NSAIDs may exert similar effects as these drugs are nonselective inhibitors of both COX‐1 and COX‐2 . Further, non‐aspirin NSAIDs are primarily used for moderate to severe pain, and, as noted, pain increases the risk of diverse mood and anxiety disorders …”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, higher doses of aspirin might inhibit COX‐2 and thereby increases leukocyte recruitment into the brain potentially causing tissue damage . The non‐aspirin NSAIDs may exert similar effects as these drugs are nonselective inhibitors of both COX‐1 and COX‐2 . Further, non‐aspirin NSAIDs are primarily used for moderate to severe pain, and, as noted, pain increases the risk of diverse mood and anxiety disorders …”
Section: Discussionmentioning
confidence: 99%
“…The 4 studies showed a positive benefit for celecoxib at some point in the trial, although the one study conducted in Germany was plagued by a dropout rate of 50% in the celecoxib group and 60% in the placebo group (Muller et al, 2006), and of the remaining 3 studies, all of which were conducted in Iran, one showed no effect at 8 weeks (Hashemian et al, 2011); yet, for unclear reasons, in each meta-analysis, the more positive 4-week data from this study (that appear in the literature as an abstract) are included in the efficacy evaluation (Muller et al, 2006;Akhondzadeh et al, 2009;Hashemian et al, 2011;Abbasi et al, 2012). Of note, the Iranian group has also published positive data for celecoxib in OCD, acute bipolar mania, and depression in breast cancer, indicating an extraordinary efficacy that warrants further evaluation (Arabzadeh et al, 2015;Mohammadinejad et al, 2015;Shalbafan et al, 2015). Finally, there are some data to support that acetylsalicylic acid may augment the response to conventional antidepressant therapy, although this is a small literature that is in need of larger studies (Mendlewicz et al, 2006).…”
Section: Reviewmentioning
confidence: 99%
“…In addition, HDRS was administered at baseline and week 8 in order to assess changes in depressive symptoms. This clinician-rated scale contains 17 questions (measured either on 5-point or 3-point scales) that assess the severity of depression-related symptoms [24] and has been used in many trials in Iran [26][27][28][29][30][31]. Our primary outcome measure was the change in the PANSS negative subscale score from baseline to week 8 in the 2 groups.…”
Section: Discussionmentioning
confidence: 99%